Meta Analysis the Effects of Maternal Education, Residence, and Birth Delivery Place, on Exclusive Breastfeeding - Amalia, Ade; Pamungkasari, Eti Poncorini; Adriani, Rita Benya (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Health and intelligence are the main foundation for creating quality Human Resources (HR). Exclusive breastfeeding is one of the best steps to improve the quality of human resources from an early age, in the first six months of a baby's life. The success of exclusive breastfeeding is due to several factors including age, relatively low level of education, lack of utilization of health facility services, and increased marketing of formula milk in urban areas. This study aims to analyze the effect of mother's education, geographic location of mother's residence, and place of delivery on exclusive breastfeeding. Subjects and Method: The researcher uses a systematic review and meta-analysis research, by formulating the researcher's assessment in the PICO as follows. Population: Breastfeeding mothers. Intervention: basic education, rural areas, health facility services. Comparison: Higher education, urban, without health facility services. Outcome: Exclusive breastfeeding. The articles were obtained from PubMed, Google Scholar, Science Direct, MDPI, and Scopus databases. The search keywords for the article are “maternal education” AND “residence” AND “delivery place” AND “exclusive breastfeeding” AND cross-sectional. The inclusion criterias were full-text, cross-sectional study, and reported adjusted odds ratio (aOR). Data were analyzed by Review Manager application (RevMan 5.3). Results: 20 cross-sectional studies involving 107,952 lactating mothers from Asia, Europe, and Africa were selected for systematic review and meta-analysis. This meta-analysis showed that mothers with high education were 1.27 times more likely to exclusively breastfeed than mothers with low education (aOR= 1.27; 95% CI=1.01 to 1.59; p= 0.040). Mothers who live in rural areas are 2.16 times more likely to give exclusive breastfeeding than mothers who live in urban areas (aOR= 2.16; 95% CI= 1.17 to 4.01; p=0.010). Mothers who give birth in health care facilities are 1.79 times more likely to give exclusive breastfeeding compared to mothers who give birth at home (aOR= 1.79; 95% CI= 1.54 to 2.07; p=0.005) Conclusion: Maternal education, geographic location, and place of delivery increase the likelihood of exclusive breastfeeding. Keywords: maternal education, residence, delivery place, exclusive breastfeeding Correspondence: Ade Amallia. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: amalliaadelia@gmail.com. Mobile:081228466836.